Rescue Archaeological Excavations of a part of the Maritime Villa in Ribnjak Bay near Valbandon (Archaeologia Adriatica, 2022)
A part of thermal complex with floor heating system and water supply has been uncovered during a month of rescue archaeological excavations conducted in 2015 in the area of a maritime villa segment extending along the northern part of Ribnjak bay near Valbandon. Room floors were covered with mosaics, marble-lined walls were adorned with frescoes, and ceilings with stucco decorations. Building of the investigated part of the villa dates to the 1st century. In the 2nd and 3rd centuries the rooms were remodeled by building new walls to partition the 1st phase spaces or the existing walls were reinforced. Numismatic finds corroborate final abandonment of this area in the 4th century. Archaeological investigation was accompanied by preventive protection procedure of mosaics and wall mortar.
Keywords: Valbandon; Ribnaj bay; villa maritima; rescue archaeological excavations; floor mosaic